Assembly and disassembly – The module as a compositional element for a ‘new’ sustainability – The Spanish case - Claudia Pirina; Giovanni Comi; Anna Frangipane (Agathón)
This paper investigates the concept of module based on Argan’s proposed dual definition of module-measure and module-object, reflecting on architectural design by ‘elements’ from a circular economy perspective. This reflection is conducted by selecting case studies on prefabricated architecture within the Iberian context, comparing contemporary projects with selected works by 20th-century Masters, following a reverse process. These works are offered as emblematic, in a logic of interaction and ‘synthesis’ between technology and design in relation to the contemporary global challenges of sustainability and energy transition. The investigation into new ways of understanding and designing architecture introduces the method of Design for Disassembly and extends the reflection on the reuse of buildings to the individual elements they are composed of.